2017
DOI: 10.3390/ijerph14101258
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Consistent Predictors of Children’s Physical Activity

Abstract: Physical activity is pivotal for children’s health and well-being, yet participation declines across teenage years. Efforts to increase physical activity need to be strengthened to combat this, however, evidence for the design and planning of physical activity promotion in children is lacking. The aim was to identify predictors of physical activity that were relatively consistent across three different measures of physical activity, in pre- and early adolescent South Australians. This is the first study to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 48 publications
2
50
1
2
Order By: Relevance
“…This finding is in line with substantial scientific evidence -30 from 35 studies found that children's PA is associated with PA of their friends -suggesting that individuals may be guided by their friends' behaviour (Maturo & Cunningham, 2013). As conclude Best, Ball, Zarnowiecki, Stanley, and Dollman (2017), peers influence children's PA most consistently through encouragement and positive modelling. Having peers that promote PA involvement and the perception that one's peers are open to PA were found to be linked with efficacious beliefs of one's ability to overcome potential barriers to participating in PA (Fitzgerald et al, 2012).…”
Section: Tablesupporting
confidence: 86%
“…This finding is in line with substantial scientific evidence -30 from 35 studies found that children's PA is associated with PA of their friends -suggesting that individuals may be guided by their friends' behaviour (Maturo & Cunningham, 2013). As conclude Best, Ball, Zarnowiecki, Stanley, and Dollman (2017), peers influence children's PA most consistently through encouragement and positive modelling. Having peers that promote PA involvement and the perception that one's peers are open to PA were found to be linked with efficacious beliefs of one's ability to overcome potential barriers to participating in PA (Fitzgerald et al, 2012).…”
Section: Tablesupporting
confidence: 86%
“…Although most of the negative health effects connected with low PAL develop later in life, lifelong patterns related to health behavior are established during childhood and adolescence [3]. Therefore, the promotion of reaching an appropriate PAL should begin at an early age [4]. For this reason, there is growing interest in research focusing on factors associated with PAL in different periods of life, and one of the promising approaches is the identification of the factors associated with "changes in PAL" over a certain period of time [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are in line with previous studies based on the self-determination theory [ 12 ]. In addition, previous studies showed that other extrinsic factors also had an important role, e.g., neighbourhood and environment [ 37 ], classmate and teacher support during physical education lessons [ 38 , 39 ] and support by family and peers [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%